A Healing Journey toward Oneself: Paul Ricoeur’s Narrative Turn in the Hermeneutics of Education - Wierciński, Andrew (ETHICS IN PROGRESS, 2010)
Narrative Mode of Understanding: Education as the Bildung of Humanity of the Human Being We all witness the inadequacy of pragmatic, approved short term solutions to complex problems of educational systems at different levels. It is predominantly the mentality of efficiency and efficacy, healing which primarily directs main attention to a practical question of ?what needs to be done? to achieve the best results in a possibly shortest time with a minimal personal, visit this social, and financial involvement